Identifikasi Penggunaan Lahan Menggunakan Metode Klasifikasi Maksimum Likelihood Pada Citra Satelit Landsat 8 OLI/TIRS Di Kabupaten Lamandau Provinsi Kalimantan Selatan Tengah - Nadia Anugrahi Lestari; Ichsan Ridwan; Fahruddin Fahruddin (Universitas Lambung Mangkurat, 2021)
Land use is a form of the influence of human activities on part of the physical surface of the earth. Land use will increase if the population increases. Activities carried out by humans can be in the form of building settlements, plantations and agriculture and cannot be separated from spatial problems because they are related to land use. Research aims to identify the land use and create distribution maps of land use in the district of Central Kalimantan province Lamandau using Landsat Satellite Imagery 8 OLI/TIRS. The land use classification uses the maximum likelihood classification method. The result of this research is a map of land use distribution in Lamandau Regency which has an area of approximately 486,738 ha. The results of this study obtained 7 classes of land use in Lamandau Regency, namely forests with an area of 182,383 ha, shrubs 118,263 ha, oil palm plantations 74,666 ha, mixed gardens 51,117 ha, settlements 28,742 ha, agriculture 28,087 ha and rivers 3,480 ha.